STATUS OF HEAVY METAL CONTAMINATION IN MAJOR RIVERS OF KERALA, SOUTH INDIA – A REVIEW - MATHEW, SOJOMON; RADHIKA, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
In the past few years, rapid urbanization and industrialization have led to an enormous increase in the amount of industrial waste generated, including heavy metals. Metal contaminants are usually found in a variety of sources, including soils, sediments and water. Rivers are the major source of fresh water for drinking, domestic needs, irrigation, industries etc. Kerala is home to 44 rivers, most of which are now polluted to a great extent due to anthropogenic activities. This manuscript reviews the research work on the heavy metal status of 10 rivers in Kerala. The levels of heavy metals such as lead (Pb), cadmium (Cd), copper (Cu), mercury (Hg), iron (Fe), manganese (Mn), nickel (Ni) etc. are increasing substantially in rivers of Kerala. Heavy metals cause irrevocable damage to the biota, when they are transferred from water bodies to the food chain via assimilation, bioaccumulation and biomethylation processes.